Evaluación energética comparativa de un sistema híbrido eólicofotovoltaico de baja potencia para la electrificación de una vivienda rural - Pacco, Karina (2019)
This work is based on the thesis titled "Comparative Energy evaluation of a hybrid wind-photovoltaic system of low power for the electrification of rural housing" conducted during February-March 2010, aims to evaluate wind and solar resources of the province of Tacna and benchmark wind-photovoltaic system with its subsystems for the electrification of a rural home located in the province of Tacna. The research used a wind turbine Rutland WG-910 and a Siemens solar panel, built instruments such as the voltage divider and the circuit Photoelectric developed a software template for the detailed study of solar and wind resources, energy systems and meteorological data, and also shows details of the technology of wind-photovoltaic hybrid system so that the hybrid system for housing projected into the near future more efficiently and economically. The subsystems that make up the hybrid wind-photovoltaic are home generators of economic power that are installed at low cost and help to free the citizens of the dependence of the power companies and oil. The results of the evaluation indicate the possibility of greater use of solar energy and non-viability of wind power for the province of Tacna, so if you make a reconversion to renewable energy, solar energy could be the new sustainable energy vector in the province of Tacna to its high material progress and sustainable development. Thus we also analyzed the technical and economic feasibility of production of each subsystem and used a method based on evaluating the reliability of an autonomous system using the concept of Loss of Load Probability, usually referred LLP. At present, on a global scale, the power consumed by humans comes from fossil fuels whose massive use leads depletion of reserves and involve both a real danger to the environment, manifesting mainly through the global warming of the earth and the acidification of the water cycle. It is important to energy conversion to energy independent, clean oil to break the economic dependence on suppliers of fossil fuels and go for sustainable development. The objective of this research is to make a “Comparative Energy evaluation of a hybrid wind-photovoltaic system of low power for the electrification of rural housing” located in the province of Tacna, for it is necessary to analyze the meteorological parameters of wind speed and local solar radiation and energy analysis and possible applications of wind-photovoltaic hybrid system, considered as an alternative to the energy sector. Throughout the collection of data and elaboration of the thesis report, it developed a software detailed study of solar and wind resources, energy systems and meteorological data.